169 IMPLEMENTATION OF BUBBLE NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE IN A COMMUNITY REFERRAL HOSPITAL. (1st January 2005) - Friedman, C. A.
Abstract : Bubble nasal continuous positive airway pressure (BnCPAP) is a management strategy for newborns with respiratory distress syndrome (RDS), either as early initial treatment to prevent intubation (Type 1) or to prevent reintubation after weaning from ventilator support (Type 2). Prevention of chronic lung disease (CLD) by minimizing mechanical ventilation is the goal of BnCPAP. The purpose of this study was to document clinical factors that may predict success of BnCPAP in a neonatal intensive care unit (NICU), thus identifying patients likely to benefit with respect to CLD. Method: Retrospective chart review of newborns admitted to a referral NICU requiring respiratory support. Results: There were 86 patients with 93 applications of BnCPAP (average estimated gestational age [EGA] 30.5 weeks, range 25-37 weeks, and average birth weight [BW] 1527 gm, range 480-5015 g). Patients < 30 weeks EGA and < 1251 g BW had higher BnCPAP failure rates than older, larger newborns, requiring intubation (Type 1: 33% vs 22%; Type 2: 44% vs 17%, p < .05, relative risk [RR] 1.75 and 3.75, respectively). Among those who failed BnCPAP, more had CLD (remained oxygen dependent at 36 weeks CGA), 50% vs 31%, p < .01, RR 1.8. For 38 patients with Type 1 BnCPAP applied during the first postnatal day, the average first day oxygenation index (OI) was lower and arterial/alveolar (a/A) estimated oxygenation ratio was higher among patients with BnCPAP success than those who failed but these differences did not reach statistical significance in predicting Type 1 outcome, p = .09. The most common causes for both types of BnCPAP failures were respiratory failure (35% of failures), nasal abrasions (22 %), and abdominal distention (17%). There were 2 deaths, 3 pneumothoraces, and 1 case of necrotizing enterocolitis among study patients. Conclusions: Successful BnCPAP is associated with greater EGA, larger BW, and lower risk of CLD. Careful attention to placement of nasal prongs and evacuation of gastric air could potentially reduce failures and decrease the risk of CLD.